Analisis Pengaruh Atmosfer Café Dan Customer Experience Terhadap Pengambilan Keputusan Customer Yaitu Mahasiswa Malang Dalam Pemilihan Tempat Coffee Shop Untuk Belajar - Fitriza Ferunita Koto; Gita Sari Agape Soebijakto; Erica Adriana (Pusat Riset dan Inovasi Nasional, 2023)
Indonesia is one of the coffee-producing countries as well as coffee connoisseurs who get attention from local and international communities. The culture of drinking coffee is enjoyed by all people in the world, but as time has progressed, the meaning of coffee drinking culture has become its meaning. The existence of this coffee drinking culture also creates a place to enjoy coffee and lifestyle activities for consumers called coffee shops or coffee shops and makes this a research subject. Research that has been done produces several things in influencing customer decision making. This research is expected to provide an understanding of customer decision making in choosing a coffee shop location to enjoy a cup of coffee and other activities, namely the café atmosphere and customer experience.